The venous and lymphatic systems of frogs and turtles in the water load (Experimental biology, 2015)
This article discusses the state of the venous and lymphatic systems of frogs and turtles in the water load. Revealed involvement of venous and lymphatic systems of frogs and turtles in the redistribution of water during the water load, and the resorption of water and its deposition in the lymphatic bed were greater than in the venous line. Venous and lymphatic system plays an important role in the transport and deposition of fl uid in the water load in lower vertebrates. In this experiments have investigated the role of the lymphatic and venous systems in lower vertebrates (Rana ridibunda and Testudo grosfi elldi) in the water exchange. It was showed that the changed in the lymphatic systems in lower vertebrates have been more observe than venous system in hypervolemia. Participation of the lymphatic and venous systems of lower vertebrates in the water exchange is similar to the process in mammals. However, the lower the potential kidney in lower vertebratesslows down the process of normalization after the water load. They have temporal characteristics of hemodynamic changes and limfodinamiki longer than in mammals.
Keywords: venous systems; lymphatic systems; amphibios; water load